SIMULATIONS OF LARGE-SCALE GASEOUS STRUCTURES WITH SPH - Sotnikova, N. Ya. (Одеські астрономічні публікації, 2017)
A computer programme based on the 3D SPH approach is described. Some numerical results are presented: the formation of gaseous ring around an SO galaxy due to the stripping of a gas-rich donor system. It is found that the ring structure strongly depends on the detailed structure of the recipient object. With the same impact parameters, rings forming around galaxies with a strong concentration of mass to the center should be less extended (on the average) than that around galaxies with a more gently sloping density profile. This inference explains in a quite natural manner the absence of extended polar rings around elliptical galaxies.